Lithium Storage Mechanism and Application of Micron‐Sized Lattice‐Reversible Binary Intermetallic Compounds as High‐Performance Flexible Lithium‐Ion Battery Anodes (Small 2/2022). Issue 2 (13th January 2022) - Fang, Zhenhan; Duan, Shaorong; Liu, Haitao; Hong, Zixin; Wu, Hengcai; Zhao, Fei; Li, Qunqing; Fan, Shoushan; Duan, Wenhui; Wang, Jiaping
Abstract : Lithium–Ion Batteries In article number 2105172, Jiaping Wang and co‐workers propose lattice‐reversible binary intermetallic compounds with zinc blende structure as a promising anode material for high‐performance flexible lithium–ion batteries. The micron‐sized indium antimonide/carbon nanotube electrodes with low volume expansion demonstrate outstanding cycle stability, rate performance, and flexibility.